Maternal parity and exclusive breastfeeding history are significantly associated with stunting in children aged 12-59 months - Syuhrotut Taufiqoh; Purnomo Suryantoro; Herlin Fitriana Kurniawati (Majalah Obstetri dan Ginekologi, 2017)
Objectives: To determine the relationship between maternal parity and exclusive breastfeeding history with stunting among children aged 12-59 months.Materials and Methods: Observational method with case control approach. Sampling method used purposive sampling was conducted in 118 children. Data were collected by observation and interview using questionnaire. Chi square test used to bivariate analysis and logistic regression used to multivariate analysis with 5% significance limit and 95% confidence level.Results: Multivariate analysis results that maternal parity and exclusive breastfeeding history was significantly associated with stunting (OR 3,419 (CI 95%: 1.433-8.156); OR 3,706 (CI 95%:1.430-9.605). External variable significantly associated with stunting is maternal occupation OR 2,972 (CI 95%: 1.285-6.874).Conclusion: Maternal parity and exclusive breastfeeding history are significantly associated with stunting in children aged 12-59 months.